Ecotonal gradients shape biodiversity of multiple estuarine taxa - Rebecca Oester; Benjamin Branoff; Johanna Biederbick; Luise Grüterich; Raphael Koll; Fay Lexmond; Nele Martens; Julian Mittmann-Goesele; Friederike Neiske; Widhi Putri; Sina Remmers; Diana Richter; et al. (Estuarine, Coastal and Shelf Science, 2026)

Long-Term Utilization of OnabotulinumtoxinA for the Treatment of Overactive Bladder - Anjali Kapur; Kimberly Becker Ifantides; Julie Zhao; Emma Yue; Ahunna Ukah; Benjamin Brucker (Toxicon, 2026)

State and trait serotonin variations interact to shape the intrinsic connectivity and gradient architecture of the brain – a combined TPH2 genetics and tryptophan depletion study in men - Lan Wang; Congcong Liu; Xianyang Gan; Keith Kendrick; Weihua Zhao; Christian Montag; Ting Xu; Benjamin Becker (Psychopharmacology, 2026)
Rationale Serotonin (5-HT) critically regulates cognitive and emotional functions, and both stable and transient variations in 5-HT signaling have been associated with emotional dysregulations. However, findings regarding the neurofunctional effects of transient 5-HT variations have been highly inconsistent. Objective Therefore, we examined whether individual variations in a central 5-HT-regulating genetic polymorphism (tryptophan hydroxylase 2, TPH2) represent a vulnerability or resilience factor for the effects of acute tryptophan depletion (ATD) on functional brain architecture. Methods The current study utilized a pharmacogenetic within-subject randomized placebo-controlled resting-state fMRI design with N = 53 healthy male participants in combination with spontaneous intrinsic neural activity, functional connectivity, and connectome gradient analyses to compare the neurofunctional effects of ATD-induced transient reduction in central 5-HT signaling between TPH2 genotypes (a priori genotyping for rs4570625, GG n = 25 vs. TT n = 23). Results ATD induced significant increases in spontaneous neural activity in hippocampal CA1 irrespective of genotype and enhanced communication of this region with the bilateral amygdala and the vmPFC specifically in GG carriers. ATD sharpened the intrinsic connectome gradient architecture in several large-scale networks, including the salience, frontoparietal, and default mode network. Conclusions Our results identify a potential genetic marker for an increased vulnerability to the neural effects of transient variations in 5-HT signaling on the functional architecture of an anxiety- and stress-related brain circuit in men. Gradient architecture results underscore the regulatory role of 5-HT on the intricate organization of large-scale networks involved in emotional reactivity and regulation.

Two-year real-world retrospective safety evaluation with onabotulinumtoxinA across multiple therapeutic indications: Findings from the SYNCHRONIZE study - Grace Forde; Kimberly Becker Ifantides; Angeli Mayadev; Atul T. Patel; Christopher Rhyne; Theodore Brown; Ritu Singh; Mariana Nelson; Ahunna Ukah; Simona Battucci; Benjamin M. Brucker (Toxicon, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Assessing risk of groundwater pollution exposure from sea level rise in California - Benjamin Hagedorn; Mark Pratt; Conor Sweeney; Matt Becker; Danielle Bram; Ben Chou; Aaron Gaines (Science of The Total Environment, 2025)

Miocene marine vertebrate trophic ecology reveals megatooth sharks as opportunistic supercarnivores - Jeremy McCormack; Iris Feichtinger; Benjamin T. Fuller; Klervia Jaouen; Michael L. Griffiths; Nicolas Bourgon; Harry Maisch; Martin A. Becker; Jürgen Pollerspöck; Oliver Hampe; Gertrud E. Rössner; Alexandre Assemat; et al. (Earth and Planetary Science Letters, 2025)

Distinct neural networks of emotional valence and uncertainty in the human amygdala underlying different mental disorders - Shitong Xiang; Chao Xie; Xiao Xiao; Tobias Banaschewski; Gareth J. Barker; Arun L.W. Bokde; Herta Flor; Antoine Grigis; Hugh Garavan; Penny Gowland; Andreas Heinz; Rüdiger Brühl; et al. (Science Bulletin, 2025)

Forensic evaluation of tail-bite wounds in pigs in Denmark - Christoffer K. Flyger; Cecilie B. Becker; Benjamin M. Jørgensen; Henrik E. Jensen (Journal of Comparative Pathology, 2025)

Developmental exposure of zebrafish to saxitoxin causes altered expression of genes associated with axonal growth - Neelakanteswar Aluru; Daniel P. Chapman; Kevin W. Becker; Benjamin A.S. Van Mooy; Sibel I. Karchner; John J. Stegeman; Mark E. Hahn (NeuroToxicology, 2024)

Refining submarine groundwater discharge analysis through nonlinear quantile regression of geochemical time series - Benjamin Hagedorn; Matthew W. Becker; Nyssa J. Silbiger; Brittney Maine; Ellen Justis; Danielle M. Barnas; Maya Zeff (Journal of Hydrology, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Lipid biochemical diversity and dynamics reveal phytoplankton nutrient-stress responses and carbon export mechanisms in mesoscale eddies in the North Pacific Subtropical Gyre - Shavonna M. Bent; Daniel Muratore; Kevin W. Becker; Benedetto Barone; Tara Clemente; Helen F. Fredricks; Henry C. Holm; David M. Karl; Benjamin A. S. Van Mooy (Frontiers in Marine Science, 2024)
Mesoscale eddies cause deviations from the background physical and biogeochemical states of the oligotrophic oceans, but how these perturbations manifest in microbial ecosystem functioning, such as community macromolecular composition or carbon export, remains poorly characterized. We present comparative lipidomes from communities entrained in two eddies of opposite polarities (cyclone–anticyclone) in the North Pacific Subtropical Gyre (NPSG). A previous work on this two-eddy system has shown differences in particulate inorganic carbon (PIC) and biogenic silica sinking fluxes between the two eddies despite comparable total organic carbon fluxes. We measured the striking differences between the lipidomes of suspended and sinking particles that indicate taxon-specific responses to mesoscale perturbations. Specifically, cyanobacteria did not appear to respond to increased concentrations of phosphorus in the subsurface of the cyclonic eddy, while eukaryotic microbes exhibit P-stress relief as reflected in their lipid signatures. Furthermore, we found that two classes of lipids drive differences between suspended and sinking material: sinking particles are comparatively enriched in phosphatidylcholine (PC, a membrane-associated lipid) and triacylglycerol (TAG, an energy storage lipid). We observed significantly greater export of TAGs from the cyclonic eddy as compared to the anticyclone and found that this flux is strongly correlated with the concentration of ballast minerals (PIC and biogenic silica). This increased export of TAGs from the cyclone, but not the anticyclone, suggests that cyclonic eddy perturbations may be a mechanism for the delivery of energy-rich organic material below the euphotic zone.

Electrochemical/computational analysis and the derivation of Pourbaix diagrams of redox-active structural and adsorbed species in uranyl peroxide clusters (U60) - Benjamin B. Gebarski; Udo Becker (Geochimica et Cosmochimica Acta, 2024)

Modelling passive sampling of hydrophilic compounds under time-variable aqueous concentrations - Benjamin Becker; Christian Kochleus; Denise Spira; Julia Bachtin; Fabian König; Stefan Meinecke; Christel Möhlenkamp; Kees Booij (Environmental Science and Pollution Research, 2024)
Passive sampling is a crucial method for evaluating concentrations of hydrophilic organic compounds in the aquatic environment, but it is insufficiently understood to what extent passive samplers capture the intermittent emissions that frequently occur for this group of compounds. In the present study, silicone sheets and styrene-divinyl benzene-reversed phase sulfonated extraction disks with and without a polyethersulfone membrane were exposed under semi-field conditions in a 31 m 3 flume at three different flow velocities. Natural processes and spiking/dilution measures caused aqueous concentrations to vary strongly with time. The data were analyzed using two analytical models that account for these time-variable concentrations: a sampling rate model and a diffusion model. The diffusion model generally gave a better fit of the data than the sampling rate model, but the difference in residual errors was quite small (median errors of 19 vs. 25% for silicone and 22 vs. 25% for SDB-RPS samplers). The sampling rate model was therefore adequate enough to evaluate the time-integrative capabilities of the samplers. Sampler performance was best for SDB-RPS samplers with a polyethersulfone membrane, despite the occurrence of lag times for some compounds (0.1 to 0.4 days). Sampling rates for this design also spanned a narrower range (80 to 110 mL/day) than SDB-RPS samplers without a membrane (100 to 660 mL/day). The effect of biofouling was similar for all compounds and was consistent with a biofouling layer thickness of 150 µm.

Modeling coupled dynamics of an empirical predator-prey system to predict top predator recovery - Samantha N.M. Hamilton; M. Tim Tinker; Joseph Jackson; Joseph A. Tomoleoni; Michael C. Kenner; Julie L. Yee; Tom W. Bell; Max C.N. Castorani; Benjamin H. Becker; Brent B. Hughes (Biological Conservation, 2024)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Medial prefrontal and occipito-temporal activity at encoding determines enhanced recognition of threatening faces after 1.5 years - Xiqin Liu; Xinqi Zhou; Yixu Zeng; Jialin Li; Weihua Zhao; Lei Xu; Xiaoxiao Zheng; Meina Fu; Shuxia Yao; Carlo V. Cannistraci; Keith M. Kendrick; Benjamin Becker (Brain Structure and Function, 2022)

Chemerin regulates normal angiogenesis and hypoxia-driven neovascularization - Cyrine Ben Dhaou; Kamel Mandi; Mickaël Frye; Angela Acheampong; Ayoub Radi; Benjamin De Becker; Mathieu Antoine; Nicolas Baeyens; Valérie Wittamer; Marc Parmentier (Angiogenesis, 2022)
Chemerin is a multifunctional protein initially characterized in our laboratory as a chemoattractant factor for leukocyte populations. Its main functional receptor is CMKLR1. We identified previously chemerin as an anti-tumoral factor inhibiting the vascularization of tumor grafts. We show here that overexpression of bioactive chemerin in mice results in a reduction of the density of the retinal vascular network during its development and in adults. Chemerin did not affect vascular sprouting during the post-natal development of the network, but rather promoted endothelial cell apoptosis and vessel pruning. This phenotype was reversed to normal in CMKLR1-deficient mice, demonstrating the role of this receptor. Chemerin inhibited also neoangiogenesis in a model of pathological proliferative retinopathy, and in response to hind-limb ischemia. Mechanistically, PTEN and FOXO1 antagonists could almost completely restore the density of the retinal vasculature, suggesting the involvement of the PI3-kinase/AKT pathway in the chemerin-induced vessel regression process.

Prochlorococcus extracellular vesicles: molecular composition and adsorption to diverse microbes - Steven J. Biller; Rachel A. Lundeen; Laura R. Hmelo; Kevin W. Becker; Aldo A. Arellano; Keven Dooley; Katherine R. Heal; Laura T. Carlson; Benjamin A. S. Van Mooy; Anitra E. Ingalls; Sallie W. Chisholm (Environmental Microbiology, 2022)
Summary Extracellular vesicles are small (~50–200 nm diameter) membrane‐bound structures released by cells from all domains of life. While vesicles are abundant in the oceans, their functions, both for cells themselves and the emergent ecosystem, remain a mystery. To better characterize these particles – a prerequisite for determining function – we analysed the lipid, protein, and metabolite content of vesicles produced by the marine cyanobacterium Prochlorococcus . We show that Prochlorococcus exports a diverse array of cellular compounds into the surrounding seawater enclosed within discrete vesicles. Vesicles produced by two different strains contain some materials in common, but also display numerous strain‐specific differences, reflecting functional complexity within vesicle populations. The vesicles contain active enzymes, indicating that they can mediate extracellular biogeochemical reactions in the ocean. We further demonstrate that vesicles from Prochlorococcus and other bacteria associate with diverse microbes including the most abundant marine bacterium, Pelagibacter . Together, our data point toward hypotheses concerning the functional roles of vesicles in marine ecosystems including, but not limited to, possibly mediating energy and nutrient transfers, catalysing extracellular biochemical reactions, and mitigating toxicity of reactive oxygen species.

Altered cerebrovascular reactivity due to respiratory rate and breath holding: a BOLD-fMRI study on healthy adults - Kai Chen; Hang Yang; Heming Zhang; Chun Meng; Benjamin Becker; Bharat Biswal (Brain Structure and Function, 2021)

Cognitive benefits of exercise interventions: an fMRI activation likelihood estimation meta-analysis - Qian Yu; Fabian Herold; Benjamin Becker; Ben Klugah-Brown; Yanjie Zhang; Stephane Perrey; Nicola Veronese; Notger G. Müller; Arthur F. Kramer; Liye Zou (Brain Structure and Function, 2021)

Intranasal oxytocin decreases fear generalization in males, but does not modulate discrimination threshold - Haoran Dou; Liye Zou; Benjamin Becker; Yi Lei (Psychopharmacology, 2021)

Passive sampler phases for pesticides: evaluation of AttractSPE™ SDB-RPS and HLB versus Empore™ SDB-RPS - Benjamin Becker; Christian Kochleus; Denise Spira; Christel Möhlenkamp; Julia Bachtin; Stefan Meinecke; Etiënne L. M. Vermeirssen (Environmental Science and Pollution Research, 2021)
In this study, three different passive sampling receiving phases were evaluated, with a main focus on the comparability of established styrene-divinylbenzene reversed phase sulfonated (SDB-RPS) sampling phase from Empore™ (E-RPS) and novel AttractSPE™ (A-RPS). Furthermore, AttractSPE™ hydrophilic-lipophilic balance (HLB) disks were tested. To support sampling phase selection for ongoing monitoring needs, it is important to have information on the characteristics of alternative phases. Three sets of passive samplers (days 1–7, days 8–14, and days 1–14) were exposed to a continuously exchanged mixture of creek and rainwater in a stream channel system under controlled conditions. The system was spiked with nine pesticides in two peak scenarios, with log K OW values ranging from approx. − 1 to 5. Three analytes were continuously spiked at a low concentration. All three sampling phases turned out to be suitable for the chosen analytes, and, in general, uptake rates were similar for all three materials, particularly for SDB-RPS phases. Exceptions concerned bentazon, where E-RPS sampled less than 20% compared with the other phases, and nicosulfuron, where HLB sampled noticeably more than both SDB-RPS phases. All three phases will work for environmental monitoring. They are very similar, but differences indicate one cannot just use literature calibration data and transfer these from one SDB phase to another, though for most compounds, it may work fine. Graphical abstract

Evidence of freshened groundwater below a tropical fringing reef - Benjamin Hagedorn; Matthew W. Becker; Nyssa J. Silbiger (Hydrogeology Journal, 2020)

Discrepancies in Flood Modelling Approaches in Transboundary River Systems: Legacy of the Past or Well-grounded Choices? - Vasileios Kitsikoudis; Bernhard P. J. Becker; Ymkje Huismans; Pierre Archambeau; Sébastien Erpicum; Michel Pirotton; Benjamin Dewals (Water Resources Management, 2020)

Particulate Organic Carbon Deconstructed: Molecular and Chemical Composition of Particulate Organic Carbon in the Ocean - Jenan J. Kharbush; Hilary G. Close; Benjamin A. S. Van Mooy; Carol Arnosti; Rienk H. Smittenberg; Frédéric A. C. Le Moigne; Gesine Mollenhauer; Barbara Scholz-Böttcher; Igor Obreht; Boris P. Koch; Kevin W. Becker; Morten H. Iversen; et al. (Frontiers in Marine Science, 2020)

A dimensional approach to jealousy reveals enhanced fronto-striatal, insula and limbic responses to angry faces - Xiaoxiao Zheng; Lizhu Luo; Jialin Li; Lei Xu; Feng Zhou; Zhao Gao; Benjamin Becker; Keith M. Kendrick (Brain Structure and Function, 2019)

Constraining the Oceanic Uptake and Fluxes of Greenhouse Gases by Building an Ocean Network of Certified Stations: The Ocean Component of the Integrated Carbon Observation System, ICOS-Oceans - Tobias Steinhoff; Thanos Gkritzalis; Siv K. Lauvset; Steve Jones; Ute Schuster; Are Olsen; Meike Becker; Roberto Bozzano; Fabio Brunetti; Carolina Cantoni; Vanessa Cardin; Denis Diverrès; et al. (Frontiers in Marine Science, 2019)

A domain-general brain network underlying emotional and cognitive interference processing: evidence from coordinate-based and functional connectivity meta-analyses - Taolin Chen; Benjamin Becker; Julia Camilleri; Li Wang; Shuqi Yu; Simon B. Eickhoff; Chunliang Feng (Brain Structure and Function, 2018)

Integrating real-time subsurface hydrologic monitoring with empirical rainfall thresholds to improve landslide early warning - Benjamin B. Mirus; Rachel E. Becker; Rex L. Baum; Joel B. Smith (Landslides, 2018)

Altered orbitofrontal activity and dorsal striatal connectivity during emotion processing in dependent marijuana users after 28 days of abstinence - Kaeli Zimmermann; Shuxia Yao; Marcel Heinz; Feng Zhou; Wolfgang Dau; Markus Banger; Bernd Weber; René Hurlemann; Benjamin Becker (Psychopharmacology, 2018)

Pan‐Arctic sea ice‐algal chl a biomass and suitable habitat are largely underestimated for multiyear ice - Benjamin A. Lange; Hauke Flores; Christine Michel; Justin F. Beckers; Anne Bublitz; John Alec Casey; Giulia Castellani; Ido Hatam; Anke Reppchen; Svenja A. Rudolph; Christian Haas (Global Change Biology, 2017)
There is mounting evidence that multiyear ice ( MYI ) is a unique component of the Arctic Ocean and may play a more important ecological role than previously assumed. This study improves our understanding of the potential of MYI as a suitable habitat for sea ice algae on a pan‐Arctic scale. We sampled sea ice cores from MYI and first‐year sea ice ( FYI ) within the Lincoln Sea during four consecutive spring seasons. This included four MYI hummocks with a mean chl a biomass of 2.0 mg/m 2 , a value significantly higher than FYI and MYI refrozen ponds. Our results support the hypothesis that MYI hummocks can host substantial ice‐algal biomass and represent a reliable ice‐algal habitat due to the (quasi‐) permanent low‐snow surface of these features. We identified an ice‐algal habitat threshold value for calculated light transmittance of 0.014%. Ice classes and coverage of suitable ice‐algal habitat were determined from snow and ice surveys. These ice classes and associated coverage of suitable habitat were applied to pan‐Arctic CryoSat‐2 snow and ice thickness data products. This habitat classification accounted for the variability of the snow and ice properties and showed an areal coverage of suitable ice‐algal habitat within the MYI ‐covered region of 0.54 million km 2 (8.5% of total ice area). This is 27 times greater than the areal coverage of 0.02 million km 2 (0.3% of total ice area) determined using the conventional block‐model classification, which assigns single‐parameter values to each grid cell and does not account for subgrid cell variability. This emphasizes the importance of accounting for variable snow and ice conditions in all sea ice studies. Furthermore, our results indicate the loss of MYI will also mean the loss of reliable ice‐algal habitat during spring when food is sparse and many organisms depend on ice‐algae.

Survival probabilities and movements of harbor seals in central California - Suzanne C. Manugian; Denise Greig; Derek Lee; Benjamin H. Becker; Sarah Allen; Mark S. Lowry; James T. Harvey (Marine Mammal Science, 2017)
Harbor seal numbers and population trajectories differ by location in central California. Within San Francisco Bay ( SFB ) counts have been relatively stable since the 1972 Marine Mammal Protection Act, but in coastal areas like Tomales Bay ( TB ), counts increased before stabilizing in the 1990s. Emigration, poor survival, and environmental effects have been hypothesized as contributors to differences between trajectories; however, basic demographic data were not available to evaluate these hypotheses. We monitored 32 radio‐tagged adult females ( SFB n = 17, TB n = 15) for 20 mo (2011–2013), and estimated survival, resight, and movement probabilities using mark‐resight analyses and multistate mark‐resight models. Annual survival probability for both sites was 0.90 (95% CI = 0.18–0.99). Six seals were observed moving between locations resulting in an estimated probability of 0.042 (95% CI = 0.023–0.076) per month equal movement between sites. Resight probability was less in SFB relative to TB , likely due to differential haul‐out access, area surveyed, visibility, and resight effort. Because of wide confidence intervals and low precision of these first estimates of adult female harbor seal survival in California, this demographic must be further examined to dismiss its contribution to differing population trajectories. Using aerial survey data, we estimated 950 harbor seals in SFB (95% CI = 715–1,184) confirming numbers are still stable.

Fabrication and Characterization of Deformable Porous Matrices with Controlled Pore Characteristics - Benjamin Munro; Sid Becker; Marc Florian Uth; Niklas Preußer; Heinz Herwig (Transport in Porous Media, 2015)

A longitudinal study of self-reported psychopathology in early ecstasy and amphetamine users - Daniel Wagner; Philip Koester; Benjamin Becker; Euphrosyne Gouzoulis-Mayfrank; Martin Hellmich; Joerg Daumann (Psychopharmacology, 2015)

Memory-related hippocampal functioning in ecstasy and amphetamine users - Benjamin Becker; Daniel Wagner; Philip Koester; Katja Bender; Christoph Kabbasch; Euphrosyne Gouzoulis-Mayfrank; Jörg Daumann (Psychopharmacology, 2013)

Reconstruction of past methane availability in an Arctic Alaska wetland indicates climate influenced methane release during the past ~12,000 years - Matthew J. Wooller; John W. Pohlman; Benjamin V. Gaglioti; Peter Langdon; Miriam Jones; Katey M. Walter Anthony; Kevin W. Becker; Kai-Uwe Hinrichs; Marcus Elvert (Journal of Paleolimnology, 2012)

Characterization of full-length MHC class II sequences in Indonesian and Vietnamese cynomolgus macaques - Hannah M. Creager; Ericka A. Becker; Kelly K. Sandman; Julie A. Karl; Simon M. Lank; Benjamin N. Bimber; Roger W. Wiseman; Austin L Hughes; Shelby L. O’Connor; David H. O’Connor (Immunogenetics, 2011)

Altered parahippocampal functioning in cannabis users is related to the frequency of use - Benjamin Becker; Daniel Wagner; Euphrosyne Gouzoulis-Mayfrank; Elmar Spuentrup; Jörg Daumann (Psychopharmacology, 2010)

A catalogue of Triticum monococcum genes encoding toxic and immunogenic peptides for celiac disease patients - Patrizia Vaccino; Heinz-Albert Becker; Andrea Brandolini; Francesco Salamini; Benjamin Kilian (Molecular Genetics and Genomics, 2009)

Modeling the effects of El Niño, density‐dependence, and disturbance on harbor seal ( Phoca vitulina ) counts in Drakes Estero, California: 1997–2007 - Benjamin H. Becker; David T. Press; Sarah G. Allen (Marine Mammal Science, 2009)
Harbor seal ( Phoca vitulina ) haul‐out site use may be affected by natural or anthropogenic factors. Here, we use an 11‐yr (1997–2007) study of a seal colony located near a mariculture operation in Drakes Estero, California, to test for natural (El Niño‐Southern Oscillation (ENSO), density‐dependence, long‐term trends) and anthropogenic (disturbance or displacement related to oyster production activities) factors that may influence the use of haul‐out subsites. Annual mariculture related seal disturbance rates increased significantly with increases in oyster harvest ( r s = 0.55). Using generalized linear models (GLMs) ranked by best fit and Akaike's Information Criteria, ENSO and oyster production (as a proxy for disturbance/displacement) best explained the patterns of seal use at all three subsites near the mariculture operations, with effects being stronger at the two subsites closest to operations. Conversely, density‐dependence and linear trend effects poorly explained the counts at these subsites. We conclude that a combination of ENSO and mariculture activities best explain the patterns of seal haul‐out use during the breeding/pupping season at the seal haul‐out sites closest to oyster activities.

Centennial Decline in the Trophic Level of an Endangered Seabird after Fisheries Decline - BENJAMIN H. BECKER; STEVEN R. BEISSINGER (Conservation Biology, 2006)
Coastal marine ecosystems worldwide have undergone such profound transformations from overfishing that trophic interactions observed today might be artifacts of these changes. We determined whether the trophic level of an endangered seabird, the Marbled Murrelet ( Brachyramphus marmoratus ), has declined over the past 100 years after the collapse of Pacific sardine ( Sardinops sadax ) fisheries in the late 1940s and the recent declines of similar fisheries in central California. We compared stable‐isotope signatures of δ 15 N and δ 13 C in feathers of museum specimens collected before fisheries decline with values in murrelet feathers collected recently. Values of δ 15 N in prebreeding diets declined significantly, 1.4‰ or 38% of a trophic level, over the past century during cool ocean conditions and by 0.5‰ during warm conditions, whereas postbreeding values of δ 15 N were nearly constant. The δ 13 C values in prebreeding diets declined by 0.8‰, suggesting an increased importance of krill in modern compared with historic prebreeding diets, but postbreeding diets did not change. Stable‐isotope mixing models indicated that the proportion of energetically superior, high‐trophic‐level prey declined strongly whereas energetically poor, low‐trophic‐level and midtrophic‐level prey increased in the prebreeding diet in cool years when murrelet reproduction was likely to be high. Decreased prey resources have caused murrelets to fish further down on the food web, appear partly responsible for poor murrelet reproduction, and may have contributed to its listing under the U.S. Endangered Species Act.